FORMULATIONS OF THE MAIN GOAL IN LIFE: A QUALITATIVE CONTENT ANALYSIS - Koļesovs, Aleksandrs; Salima, Irina; Maskovs, Andris (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Humanistic tradition emphasizes the main goal in life as something towards which people determine themselves. The main goal (or a group of goals with the highest priority) provides the basis for the sense of purpose in life and for development of its meaning. This study aimed at revealing categories in formulations of the main goal in life. Participants were 226 adults aged from 18 to 69 (M = 25.34, SD = 8.51, 65% females). They answered an open question: “Kā Jūs raksturotu galveno dzīves mērķi? Lūdzu, padalieties ar savām pārdomām. [How could You describe the main goal in life? Please, share your opinion.]” The qualitative content analysis resulted in 29 categories. Inter-rater agreement among three raters was acceptable and varied from .72 to 1.00 (the mean Krippendorff’s alpha was .88). Work, Family, and Satisfaction were the most frequently selected categories for a formulation of the main goal, while Love, Leisure, and Transcendent Issues were the less selected ones. An additional step of thematic analysis demonstrated that categories can be joined in four overarching themes: Vague Formulations, Self, Others, and Desired States.